Surface Display of porcine circovirus type 2 antigen protein cap on the spores of bacillus subtilis 168: An effective mucosal vaccine candidate - Li, Weijie; Li, Jianzhen; Dai, Xixi; Liu, Minggang; Khalique, Abdul; Wang, Zhenghua; Zeng, Yan; Zhang, Dongmei; Ni, Xueqin; Zeng, Dong; Jing, Bo; Pan, Kangcheng (Frontiers in Immunology, 2022)
The oral mucosal vaccine has great potential in preventing a series of diseases caused by porcine circovirus type 2 (PCV2) infection. This study constructed a recombinant Bacillus subtilis RB with PCV2 Capsid protein (Cap) on its spore surface and cotB as a fusion partner. The immune properties of the re-combinant strain were evaluated in a mouse model. IgA in intestinal contents and IgG in serum were de-tected by enzyme-linked immunosorbent assay (ELISA). The results demonstrated that recombinant spores could activate strong specific mucosal and humoral immune responses. In addition, spores showed good mucosal immune adjuvant function, promoting the proliferation of CD3+, CD4+ and CD8+ T cells and other immune cells. We also found that the relative expression of inflammatory cytokines such as IL-1β, IL-6, IL-10, TNF-α and IFN in the small intestinal mucosa was significantly up-regulated under the stimu-lation of recombinant bacteriophage. These effects are important for the balance of Th1/ Th2-like re-sponses. In summary, our results suggest that recombinant B. subtilis RB as a feed additive provides a new strategy for the development of novel and safe PCV2 mucosal subunit vaccines.